The multi-layered ring under parabolic distribution of radial stresses combined with uniform internal and external pressure (Fracture and Structural Integrity, 2017)
A recently introduced solution for the stress- and displacementfields, developed in a multi-layered circular ring, composed of a finite number of linearly elastic concentric layers, subjected to a parabolic distribution of radial stresses, is here extended to encompass a more general loading scheme, closer to actual conditions. The loading scheme includes, besides the parabolic radial stresses, a combination of uniform pressures acting along the outer- and innermost boundaries of the layered ring. The analytic solution of the problem is achieved by adopting Savin’s pioneering approach for an infinite plate with a hole strengthened by rings. Taking advantage of the results provided by the analytic solution, a numerical model, simulating the configuration of a threelayered ring (quite commonly encountered in practical applications) is validated. The numerical model is then used for a parametric analysis enlightening some crucial aspects of the overall response of the ring.
Keywords: Multi-layered ring; Parabolic pressure; Stress and displacement fields; Uniform pressure; Complex potentials